Studi Kasus Perhitungan Tingkat Morbiditas, Mortalitas, dan Fatalitas Kolibasilosis pada Babi yang Dipelihara Semi-intensif - Kardena, I Made; Suarjana, I Gusti Ketut; Udayani, Putri (Buletin Veteriner Udayana, 2012)
A case study on morbidity, mortality and case fatality rate of swine colibasillosis was done. A totalof 244 pigs aged 1 day to 4 weeks that were collected from semi-intensive pig farms was used inthis study. All of the young pigs were obtained from Sudimara Village, in Tabanan District, Bali.The observation of the disease was evaluated in 30 days. Confirmation of Colibasillosis infectionwas based on the diarrhea clinical sign, and then confirmed with microbiological test using EMBA.The percentage of morbidity, mortality and case fatality rate were calculated based on the formulaof Roberson (2008). Results showed the morbidity, mortality and case fatality rate were 8.6%,2.05%, and 23.8% respectively. These results indicating that morbidity, mortality and case fatalityrate in young pigs that were rising in semi-intensive farm were relatively low. It seemed that thelow level of morbidity, mortality, and case fatality rate were influenced by the pig rising systemwhere the feed, captive, and hygiene are much better than the traditional pig farming system.
Keywords: morbidity, mortality, case fatality rate, swine colibasillosis